Efektivitas Cognitive Behavior Art Therapy untuk Mereduksi Kecemasan Remaja di LSM ‘E’ - Patriadi, Theodora Putri Antonius; Widyorini, Endang (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
Adolescents living in NGO “E” who have or are at risk of losing their parental rights experience many problems, especially problems related to anxiety. Anxiety felt by adolescents can be caused by uncertainty about the future and goals, economic difficulties, especially education costs, relationships with friends and foster families, living conditions and change of residence. The existence of different backgrounds makes adolescents need to make adjustments to their environment, both with friends and with NGO administrators. This study uses cognitive behavior art therapy to reduce anxiety in groups for adolescents living in NGOs. The participants in this study were 4 adolescent boys. Pre-test and post test in the form of DASS were given to participants to determine changes after the intervention. After 6 sessions of cognitive behavior art therapy intervention in the group, the adolescents showed a decrease in anxiety levels.